Three-dimensional flow of radiative hybrid nanofluid past a permeable stretching/shrinking sheet with homogeneous-heterogeneous reaction. Issue 2 (8th June 2021) - Khashi'ie, Najiyah Safwa; Arifin, Norihan Md; Rosca, Natalia C.; Rosca, Alin V.; Pop, Ioan
Abstract : Purpose: The purpose of this paper is to study the effects of thermal radiation and homogeneous-heterogeneous reactions in the three-dimensional hybrid nanofluid flow past a permeable stretching/shrinking sheet. Design/methodology/approach: The combination of aluminum oxide (Al2 O3 ) and copper (Cu) nanoparticles with total volumetric concentration is numerically analyzed using the existing correlations of hybrid nanofluid. With the consideration that both homogeneous and heterogeneous reactions are isothermal while the diffusion coefficients of both autocatalyst and reactant are same, the governing model is simplified into a set of differential (similarity) equations. Findings: Using the bvp4c solver, dual solutions are presented, and the stability analysis certifies the physical/real solution. The findings show that the suction parameter is requisite to induce the steady solution for shrinking parameter. Besides, the fluid concentration owing to the shrinking sheet is diminished with the addition of surface reaction. Originality/value: The present findings are novel and can be a reference point to other researchers to further analyze the heat transfer performance and stability of the working fluids.